Effect of Magnetic Treatment of Water on Evapotranspiration of Tomato - Yusuf, K. O.; Ogunlela, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2017)
This study was conducted to determine the effect of magnetic treatment of water on the evapotranspiration of tomato plant. Evapotranspiration is important to plant for metabolic processes and it also cools the plant. Three magnetic flux densities of 124, 319 and 719 G produced from electromagnet (the treatments) labelled as T1, T2 and T3 were used to treat the water and a control experiment (TC) was also set up which was irrigated with non-magnetic treatment water. Equal amount of water was applied to all the tomato plant (variety UC82B) at the same time. Each treatment was replicated seven times given a total of 28 buckets containing tomato plant. The tomato was planted in the 28 buckets in a transparent garden shed for 130 days (23/09/2014 – 30/01/2015. A complete randomized design (CRD) experimental layout was used. The amount of water lost due to evapotranspiration per day was determined by weight lost in the bucket (lysimetric weighing method). The mean values of daily evapotranspiration for two stands of tomato plants per bucket over a period of 65 days for T1, T2, T3 and TC were 9.38, 9.28, 9.18 and 8.03 mm/day respectively. The result of the evapotranspiration due to mass of water lost from the buckets containing tomato plants irrigated with magnetic water were all higher than the values of evapotranspiration from non-magnetic water. This indicated that tomato plant irrigated with magnetic treatment of water absorbed more water from the soil easily and grew faster than the tomato plant irrigated with non-magnetic treatment water with the same quantity of water applied to the tomato plant.